2006
DOI: 10.1111/j.1365-2796.2006.01637.x
|View full text |Cite
|
Sign up to set email alerts
|

Low testosterone levels are associated with carotid atherosclerosis in men

Abstract: Objective. To study the relationship between endogenous sex hormone levels and intima-media thickness (IMT) of the carotid artery measured by ultrasonography. Design. Population-based cross-sectional study. Methods. Sex hormone levels measured by immunoassay, anthropometric measurements and IMT was studied in 1482 men aged 25-84 years participating in the 1994-1995 Tromsø study. The data were analysed with partial correlation, multiple linear regression and logistic regression analysis. Results. Linear regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
3
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 42 publications
10
119
3
2
Order By: Relevance
“…Intima-media thickness (IMT, a measure of the thickness of the innermost two layers of the arterial wall) is associated with atherosclerosis and is viewed as a surrogate endpoint for evaluating the regression and/or progression of atherosclerotic CVD. Several human studies have shown that carotid IMT (CIMT) and aortic calcification negatively correlate with serum testosterone (Hak et al 2002, van den Beld et al 2003, Fukui et al 2003, Muller et al 2004, Demirbag et al 2005, Mäkinen et al 2005, Svartberg et al 2006. Low levels of testosterone in men were inversely related to the mean progression of IMT in the common carotid artery even after adjusting for age, and this relationship was found to be independent of other cardiovascular risk factors (Muller et al 2004).…”
Section: Vascular Mechanisms Of Testosteronementioning
confidence: 99%
“…Intima-media thickness (IMT, a measure of the thickness of the innermost two layers of the arterial wall) is associated with atherosclerosis and is viewed as a surrogate endpoint for evaluating the regression and/or progression of atherosclerotic CVD. Several human studies have shown that carotid IMT (CIMT) and aortic calcification negatively correlate with serum testosterone (Hak et al 2002, van den Beld et al 2003, Fukui et al 2003, Muller et al 2004, Demirbag et al 2005, Mäkinen et al 2005, Svartberg et al 2006. Low levels of testosterone in men were inversely related to the mean progression of IMT in the common carotid artery even after adjusting for age, and this relationship was found to be independent of other cardiovascular risk factors (Muller et al 2004).…”
Section: Vascular Mechanisms Of Testosteronementioning
confidence: 99%
“…In addition, low levels of androgens in men have been shown to be important risk factors for the development of the intima-media thickening in the common carotid artery even after adjusting for age, sex, and other cardiovascular risk factors 47,48) . Several human studies have also shown that the severity of aortic calcification negatively correlates with the testosterone serum level 47,[49][50][51][52][53] . Moreover, physiological concentrations of testosterone have been shown to maintain homeostasis of the hemostatic system through the enhancement of anticoagulant activity and antithrombotic effects [54][55][56] .…”
Section: Introductionmentioning
confidence: 99%
“…Low testosterone levels may predict increased cardiovascular risk in men [13]. Moreover, treatment with exogenous testosterone improved arterial vasodilation [14] and lipid profile [15] in patients with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%